Kualifikasi Welder FCAW-GS Pada Posisi 6G Menggunakan Multiple Code (AWS D1.1, ASME Sec. IX, dan ISO 9606-1) - Rafi Julio Putra; Nurul Laili Arifin; Tian Havwini; Nugroho Pratomo Ariyanto (Politeknik Negeri Batam, 2021)
Welder qualification is the qualification of a welder or welder that aims to prove the quality of the welder, which is carried out following the rules in international codes/standards such as AWS, API, ASME, ISO, and other codes/ codes/standards. The purpose of this report is to design a welder qualification scheme using three codes/standards at once, namely: AWS D1.1 (2020), ASME Sec. IX (2019) and ISO 9609-1 (2017). Thus, it can minimize costs, time, and the preparation needed to qualify the welder. The methodology used was a literature review to get the similarity of the variables, which will later be used to qualify the welder using the three codes/standards used. After obtaining the required variables, the next step was the implementation of these variables to qualify the welder from the material preparation and welding process to test the weld results. In order to qualify the welder with three codes/standards at once, it was necessary to pay attention to the relationship for each variable used to cover one code with another. If one of the variables cannot be met in one of the codes/standards used, then the welder's qualification using three codes/standards cannot be implemented. The material used in this welder qualification is ASTM A106 Grade B with a material length of 170 mm × 170 mm with a thickness of 18.26 mm and a diameter of 6